AML/CFT Compliance: Does it Influence the Influx of Foreign Direct Investment? - Nkrumah, G.A. (University of Ghana, 2019)
This study examines the relationship between countries’ compliance with AML/CFT (Anti-Money Laundering and Countering the Financing of Terrorism) regulations and foreign direct investment. This study, to the best of the author’s knowledge, is the first to establish a link between AML/CFT compliance and FDI, with FDI being the dependent variable and AML/CFT compliance, the independent. The research uses a sample size of 74 FATF member states and extracts data on their FDI net inflows and AML/CFT compliance ratings from the year 2004 to 2016. Furthermore, it employs a multiple regression analysis with five control variables. The results of the analysis indicate that a country’s compliance with AML/CFT regulations is a driver of the influx of foreign direct investment into its economy. This discovery is important because the costs of compliance – what seems to be the largest barrier – is not as challenging as it used to appear. Bearing this in mind, countries would be encouraged to put more effort into their compliance activities, instead of aiming for the minimum acceptable level, which seems to be the case at the moment. In addition, it is discovered that the market size, quality of infrastructure, quality of human capital and inflation rate are very instrumental in the attraction of FDI. Keywords: Anti-Money Laundering, Money Laundering, Terrorist Financing, Foreign Direct Investment
MPhil. Finance
Keywords: Anti-Money Laundering; Money Laundering; Terrorist Financing; Foreign Direct Investments (FDI)